β-Co(OH)2 precursor and preparation method thereof and lithium battery positive electrode material
By preparing β-Co(OH)2 precursors with different micromorphic morphology and sizes in wet synthesis method and coating them on the surface of nickel-rich cathode material by dry method, the surface and structural problems of the existing ternary layered oxide cathode material when increasing Ni content or working voltage are solved, and the effect of improving material stability and electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411931772.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
When the existing ternary layered oxide positive electrode materials increase Ni content or operating voltage, they are prone to surface and structural problems, resulting in material failure and battery safety problems.
By introducing ammonia water, long-chain polymer surfactants and quaternary ammonium salt surfactants into the wet synthesis method, β-Co(OH)2 precursors with different micromorphic morphology and sizes were prepared, and the surface of nickel-rich positive electrode material was coated to form a coating by dry method.
The surface stability, cycling performance and service life of nickel-rich cathode materials are improved, while the lithium ion diffusion capacity is enhanced, and the ion conductivity and electrical conductivity of the material are improved.
Smart Images

Figure CN119750661A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a beta-Co(OH)2 precursor and a preparation method thereof, and a lithium battery positive electrode material. Background Art
[0002] With the rapid development of electric vehicles, ternary materials for lithium-ion batteries have received extensive attention from the market and research due to their high energy density. Among them, ternary layered oxide positive electrode materials are regarded as strong competitors for high-performance lithium-ion battery positive electrode materials due to their higher energy density. As consumers have higher requirements for driving range, in order to improve the energy density of materials, the most mainstream approach is to increase the Ni content in the ternary material or to increase the working voltage of the material. Both of these approaches will cause the material to suffer from more serious surface and structural problems, and accelerate the failure of positive and negative active materials and electrolytes. At the same time, when the Ni content in the ternary material exceeds 80 mol%, the lattice Li reacts with moisture and carbon dioxide in the air through a substitution reaction to precipitate, forming residual lithium compounds on the surface of the positive electrode material, and reacts with the electrolyte in the high voltage working range to form an inert layer, which hinders Li + Spread and cause safety issues such as battery gas and heat generation. Summary of the invention
[0003] The purpose of the present invention is to provide a β-Co(OH)2 precursor and a preparation method thereof and a lithium battery positive electrode material in order to overcome the defects of the above-mentioned prior art.
[0004] The invention provides a method for preparing a β-Co(OH)2 precursor, which comprises: in the presence of a complexing agent, allowing a soluble cobalt salt and an alkaline compound to undergo a coprecipitation reaction in a solvent to obtain a β-Co(OH)2 precursor with different micromorphologies and sizes, wherein the complexing agent comprises ammonia water, a long-chain polymer surfactant and a quaternary ammonium salt surfactant.
[0005] The present invention also provides a β-Co(OH)2 precursor, which has a monomer lamellar structure and an average particle size of 0.1 μm-5.0 μm.
[0006] The present invention also provides a lithium battery positive electrode material, the surface of which is coated with the above-mentioned β-Co(OH)2 precursor or the β-Co(OH)2 precursor prepared by the above-mentioned preparation method.
[0007] The present invention has the following beneficial effects:
[0008] The present invention provides a β-Co(OH)2 precursor and a preparation method thereof and a lithium battery positive electrode material. The present invention prepares a β-Co(OH)2 precursor with different microscopic morphologies and sizes by a wet synthesis method, utilizes the physical adsorption capacity of submicron particles, and forms a coating on the surface of a nickel-rich positive electrode material by a dry coating method to improve the surface stability, cycle performance and service life of the nickel-rich positive electrode material. At the same time, the ionic conductivity and electrical conductivity of the material can be improved by enhancing the lithium ion diffusion capacity to improve the rate performance of the nickel-rich positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0010] Figure 1 is the SEM image of sample A prepared in Example 1;
[0011] Figure 2 is the SEM image of sample B prepared in Example 2;
[0012] Figure 3 is the SEM image of sample C prepared in Example 3;
[0013] Figure 4 is the SEM image of sample D prepared in Example 4;
[0014] Figure 5 is the SEM image of sample E prepared in Example 5;
[0015] Figure 6 is the SEM image of sample F prepared in Example 6;
[0016] Figure 7 This is the SEM image of sample G prepared in Comparative Example 1. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0018] The following is a detailed description of a β-Co(OH)2 precursor and a preparation method thereof and a lithium battery positive electrode material provided in an embodiment of the present invention.
[0019] In the first aspect, an embodiment of the present invention provides a method for preparing a β-Co(OH)2 precursor, which comprises: in the presence of a complexing agent, allowing a soluble cobalt salt and an alkaline compound to undergo a coprecipitation reaction in a solvent to obtain a β-Co(OH)2 precursor having different micromorphologies and sizes, wherein: the complexing agent comprises ammonia water, a long-chain polymer surfactant and a quaternary ammonium salt surfactant.
[0020] Existing optimization methods are usually ion doping, surface coating or structural design. Among them, surface coating usually uses inert coatings such as oxides, fluorides, phosphates, etc. that are not electrochemically active. Although it can hinder the contact between the electrolyte and the active material and slow down the failure caused by the surface reaction between the material and the electrolyte, this coating method reduces the overall energy density of the material and damages the rate performance of the battery. When Co is used as a coating material, its electrochemical activity can provide part of the capacity for the positive electrode material. At the same time, when it is enriched on the surface of the positive electrode material, it forms a spinel-like structure, which slows down the reaction between the active material and the electrolyte; the introduction of a coating agent in the subsequent dry coating process can reduce the residual lithium compounds on the surface of the material and remove the water washing step. The above two approaches can enhance its surface stability and ultimately increase the service life of the positive electrode material.
[0021] The embodiment of the present invention provides a method for preparing a β-Co(OH)2 precursor. During the coprecipitation reaction, ammonia water, a long-chain polymer surfactant and a quaternary ammonium salt surfactant are introduced, and different types of surfactants are used to induce the growth of the β-Co(OH)2 precursor, thereby preparing a β-Co(OH)2 precursor with different micromorphologies and sizes. The β-Co(OH)2 precursor with different micromorphologies and sizes is prepared by changing the synthesis conditions at the wet synthesis end. Experimental results show that the β-Co(OH)2 precursor with different sizes and morphologies can provide different electrical performance gains for the nickel-rich positive electrode material after being coated on the surface of the positive electrode material.
[0022] In some optional embodiments, the long-chain polymer surfactant is polyvinyl pyrrolidone, and the quaternary ammonium salt surfactant is dodecyltrimethylammonium bromide.
[0023] In some optional embodiments, the steps include: under the protection of inert gas, introducing a cobalt salt solution and an alkaline compound solution into a base liquid in parallel, wherein the base liquid optionally further contains at least one of a polyvinyl pyrrolidone solution and a dodecyltrimethylammonium bromide solution, the concentration of the polyvinyl pyrrolidone solution is 0g / L-20g / L, and the concentration of the dodecyltrimethylammonium bromide solution is 0g / L-7g / L, and a β-Co(OH)2 precursor with a particle size of 0.3μm-1.0μm is obtained through a coprecipitation reaction, and the larger single submicron particles appear as thin flakes with larger lateral dimensions, while the scattered smaller single submicron particles appear as thin and short flakes.
[0024] In some optional embodiments, the steps are included: under the protection of an inert gas, a cobalt salt solution and an alkaline compound solution are introduced into a base liquid in parallel, wherein: in addition to the cobalt salt solution and the alkaline compound solution introduced into the base liquid in parallel, an ammonia solution, a polyvinyl pyrrolidone solution and a dodecyltrimethylammonium bromide solution may also be optionally introduced, the concentration of the ammonia solution is 0g / L-5g / L, the concentration of the polyvinyl pyrrolidone is 0g / L-20g / L, and the concentration of the dodecyltrimethylammonium bromide is 0g / L-7g / L, and a β-Co(OH)2 precursor with a particle size of 0.1μm-1.0μm is obtained through a coprecipitation reaction, and a larger single submicron particle is composed of a single smaller submicron particle spliced together by dissolution and recrystallization, and presents a thick long plate with a larger lateral size; while the scattered single smaller submicron particles present a thick brick shape with a smaller lateral size.
[0025] In some optional embodiments, the steps include: under the protection of an inert gas, flowing a cobalt salt solution and an alkaline compound solution into a base liquid in parallel, wherein the base liquid optionally further contains at least one of a polyvinyl pyrrolidone solution and a dodecyltrimethylammonium bromide solution, and in addition to the cobalt salt solution and the alkaline compound solution flowing into the base liquid in parallel, an aqueous ammonia solution, a polyvinyl pyrrolidone solution and a dodecyltrimethylammonium bromide solution may also be optionally introduced, and after a coprecipitation reaction, after the reaction is completed, the concentration of the polyvinyl pyrrolidone solution in the reaction system is 0.01g / L-30g / L, the concentration of the dodecyltrimethylammonium bromide solution is 0.01g / L-10g / L, and the concentration of the aqueous ammonia solution is 0.01g / L-5g / L, and a β-Co(OH)2 precursor with a particle size of 0.1μm-0.5μm is obtained, and a single submicron particle presents a thick brick shape with a small lateral size, or a single submicron particle presents a thin blade shape with a small lateral size.
[0026] In some optional embodiments, the preparation of the basic base liquid includes: adding pure water to the reactor, introducing inert gas to replace the air, and after the air in the reactor is replaced, stirring and heating are turned on. After the temperature reaches the requirement, ammonia solution and alkali solution are added to the pure water to adjust the pH value of the solution in the reactor, wherein: the stirring speed of the base liquid is 100rpm-1000rpm, and the temperature is 20°C-80°C; the amount of pure water is 20%-60% of the total volume of the reactor, the alkali solution is sodium hydroxide solution, the hydroxide concentration in the base liquid is 0.001mol / L-2.0mol / L, and the ammonia solution concentration is 1g / L-10g / L.
[0027] In some optional embodiments, the soluble cobalt salt includes at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate, the concentration of the soluble cobalt salt solution is 1 mol / L-3 mol / L, the alkaline compound is sodium hydroxide, the concentration of the alkaline compound solution is 5 mol / L-14 mol / L, the mass ratio of the cobalt element in the soluble cobalt salt solution to the polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution is 5 to 30, and the mass ratio of the cobalt element in the soluble cobalt salt solution to dodecyltrimethylammonium bromide in the dodecyltrimethylammonium bromide solution is 30 to 120.
[0028] In some optional embodiments, the method further includes: after the coprecipitation reaction is completed, the slurry is aged and filtered, and then centrifuged and washed until the Na content in the material is ≤1000ppm and the anion content is ≤1000ppm, and then dried to a moisture content of ≤0.8% to obtain a β-Co(OH)2 precursor.
[0029] In a second aspect, an embodiment of the present invention further provides a β-Co(OH)2 precursor having a monomer lamellar structure and an average particle size of 0.1 μm-5 μm.
[0030] In a third aspect, an embodiment of the present invention further provides a lithium battery positive electrode material, the surface of which is coated with the above-mentioned β-Co(OH)2 precursor or the β-Co(OH)2 precursor prepared by the above-mentioned preparation method.
[0031] Surface coating is one of the effective methods to improve the surface stability of positive electrode materials. Through this method, a protective layer can be formed on the surface of the electrode material to inhibit the interfacial reaction between the positive electrode material and the electrolyte, and to prevent the electrode active material from being corroded by HF in the electrolyte, thereby stabilizing the surface structure of the material. Common coating compounds mainly include inert compounds such as oxides, fluorides, and phosphates, and conductive materials such as carbon-based materials and lithium-containing compounds. The thickness of the inert coating will inhibit the ion diffusion of the material, and the protective performance of conductive materials is relatively weak, and complex coating procedures and additional equipment are required. In addition, when the thickness of the conventional coating is low, the coating protection effect cannot be achieved. When the thickness is thicker, it cannot provide capacity due to lack of electrochemical activity, and does not meet the requirements of high capacity and energy density.
[0032] The embodiment of the present invention provides a lithium battery positive electrode material, the surface of which is coated with the above-mentioned β-Co(OH)2 precursor. When cobalt is used as the surface coating, it can have a favorable effect on the active material in three aspects. On the one hand, the electrochemical activity of Co can provide part of the capacity for the positive electrode material. At the same time, when it is enriched on the surface of the positive electrode material, it forms a spinel-like structure, which slows down the reaction between the active material and the electrolyte. On the other hand, the introduction of a coating agent in the subsequent dry coating process can reduce the residual lithium compounds on the surface of the material and eliminate the water washing step. The above two approaches can enhance its surface stability, ultimately improve the service life of the positive electrode material, and reduce the difficulty of procedures and processes.
[0033] The present invention changes the synthesis conditions at the wet synthesis end to prepare cobalt hydroxide nanoparticles / sheets with different microscopic morphologies and sizes, utilizes the physical adsorption capacity of submicron particles, and forms a coating on the surface of the ternary positive electrode material by dry coating. The monomer layer of the β-Co(OH)2 precursor can be embedded in the grain boundary of the secondary particles of the layered oxide positive electrode material or attached to the surface of the positive electrode material, and forms a spatially staggered protective layer through diffusion. This structure can optimize the microscopic surface stability of the active material to improve its charge and discharge cycle life and rate performance, etc., thereby improving the ionic conductivity and electrical conductivity of the positive electrode material, so as to improve the stability, rate performance and service life of the nickel-rich positive electrode material.
[0034] The present invention will be further described below in conjunction with the embodiments.
[0035] Example 1: A method for preparing a first rate type cobalt hydroxide, comprising the following steps:
[0036] (1) According to a certain concentration of a metal cobalt sulfate salt solution, the corresponding mass of cobalt sulfate is calculated, and cobalt sulfate is prepared with pure water to prepare a metal cobalt sulfate salt solution with a concentration of 2 mol / L, which is recorded as solution A;
[0037] (2) preparing a sodium hydroxide solution with a concentration of 7 mol / L as a precipitant, recorded as solution B;
[0038] (3) Configuration of auxiliary feed ①: According to a certain concentration, calculate the corresponding mass, and use pure water to prepare liquid ammonia into an ammonia solution with a concentration of 8 mol / L, which is recorded as C1 solution;
[0039] (4) Configuration of auxiliary feed ②: According to a certain concentration, calculate the corresponding mass, and use pure water to prepare PVP to a concentration of 100 g / L, which is recorded as C2 solution;
[0040] (5) Preparation of auxiliary feed ③: According to a certain concentration, calculate the corresponding mass and use pure water to prepare DTAB to a concentration of 10 g / L, which is recorded as C3 solution;
[0041] (6) Add pure water accounting for 50% of the volume of the reactor into the reactor, introduce nitrogen as a protective gas, and start the stirring and heating program: the stirring speed is 700 rpm, the temperature is 50° C., and then add a certain amount of liquid alkali and ammonia water to adjust the hydroxide concentration in the base liquid to 0.6 mol / L, the ammonia concentration to 4 g / L, and the PVP solution concentration to 5 g / L;
[0042] (7) Under the conditions of step (6), the A, B, C1, C2, and C3 solutions are simultaneously pumped into the reactor in parallel to perform precipitation reaction. The mass ratio of the cobalt salt solution to the auxiliary feed ② is: Co / M F② =24, the mass ratio of cobalt salt solution to auxiliary feed ③ is: M Co / M F③ =47, the flow rate of solution B is adjusted according to the hydroxide concentration, and the flow rate of C1 is adjusted according to the ammonia concentration, so as to always keep the concentrations of the added sodium hydroxide solution and ammonia solution consistent with those of the bottom liquid in the reactor.
[0043] (8) The slurry obtained in step (7) is filtered and washed to remove excess sulfate ion and lithium ion impurities. When Na≤1000ppm and S≤1000ppm in the sample, the sample is dried to obtain a product A.
[0044] (9) The β-Co(OH)2 product A obtained in step (8) was characterized by SEM. Figure 1 The particle size distribution is 0.1-0.5μm, and the individual submicron particles are in the shape of thick bricks with small lateral dimensions, which are evenly distributed and well dispersed.
[0045] Embodiment 2: The preparation method of comprehensive cobalt hydroxide comprises the following steps:
[0046] (1) According to the concentration of a certain metal cobalt chloride salt solution, the corresponding mass of cobalt chloride is calculated, and the salt is prepared with pure water to prepare a cobalt salt solution with a concentration of 1.6 mol / L, which is recorded as solution A;
[0047] (2) preparing a sodium hydroxide solution with a concentration of 10 mol / L as a precipitant, recorded as solution B;
[0048] (3) Configuration of auxiliary feed ①: According to a certain concentration, calculate the corresponding mass, and use pure water to prepare liquid ammonia into an ammonia solution with a concentration of 5 mol / L, which is recorded as C1 solution;
[0049] (4) Configuration of auxiliary feed ②: According to a certain concentration, calculate the corresponding mass, and use pure water to prepare PVP to a concentration of 150g / L, which is recorded as C2 solution;
[0050] (5) Preparation of auxiliary feed ③: According to a certain concentration, calculate the corresponding mass and use pure water to prepare DTAB to a concentration of 5 g / L, which is recorded as C3 solution;
[0051] (6) Add pure water accounting for 30% of the volume of the reactor into the reactor, introduce argon as a protective gas, and start the stirring and heating program: the stirring speed is 700 rpm, the temperature is 25° C., and then add a certain amount of liquid alkali and ammonia water to adjust the hydroxide concentration in the bottom liquid to 1.0 mol / L, the ammonia concentration to 1 g / L, the PVP solution concentration to 10 g / L, and the DTAB solution concentration to 6 g / L;
[0052] (7) Under the conditions of step (6), the A, B, C1, C2, and C3 solutions are simultaneously pumped into the reactor in parallel to perform precipitation reaction. The mass ratio of the cobalt salt solution to the auxiliary feed ② is: Co / M F② =12, the mass ratio of cobalt salt solution to auxiliary feed ③ is: M Co / M F③ =110, the flow rate of solution B is adjusted according to the hydroxide concentration, and the flow rate of solution C1 is adjusted according to the ammonia concentration, so as to always keep the concentrations of the added sodium hydroxide solution and ammonia solution consistent with those of the bottom liquid in the reactor.
[0053] (8) The slurry obtained in step (7) is filtered and washed to remove excess chloride ion and lithium ion impurities. When Na≤1000ppm and Cl≤1000ppm in the sample, the sample is dried to obtain a product referred to as product B.
[0054] (9) The β-Co(OH)2 product B obtained in step (8) was characterized by SEM. Figure 2The particle size is 0.1-0.5μm, and the individual submicron particles are thin and blade-shaped with small lateral dimensions, and are evenly distributed and well dispersed.
[0055] Embodiment 3: The preparation method of the second rate type cobalt hydroxide comprises the following steps:
[0056] (1) According to a certain concentration of a metal cobalt sulfate salt solution, the corresponding mass of cobalt sulfate is calculated, and cobalt sulfate is prepared with pure water to prepare a metal cobalt sulfate salt solution with a concentration of 2.5 mol / L, which is recorded as solution A;
[0057] (2) preparing a sodium hydroxide solution with a concentration of 14 mol / L as a precipitant, recorded as solution B;
[0058] (3) Configuration of auxiliary feed ①: According to a certain concentration, calculate the corresponding mass, and use pure water to prepare liquid ammonia into an ammonia solution with a concentration of 10 mol / L, which is recorded as C1 solution;
[0059] (4) Configuration of auxiliary feed ②: According to a certain concentration, calculate the corresponding mass, and use pure water to prepare PVP to a concentration of 150g / L, which is recorded as C2 solution;
[0060] (5) Preparation of auxiliary feed ③: According to a certain concentration, calculate the corresponding mass and use pure water to prepare DTAB to a concentration of 10 g / L, which is recorded as C3 solution;
[0061] (6) Add 60% pure water to the reactor and pass 0.4 m 3 / h nitrogen as protective gas, and then start the stirring and heating program: the stirring speed is 700rpm, the temperature is 70℃, and then a certain amount of liquid alkali and ammonia water are added to adjust the hydroxide concentration in the base liquid to 1.0mol / L and the ammonia concentration to 2.5g / L;
[0062] (7) Under the conditions of step (6), the A, B, C1, C2, and C3 solutions are simultaneously pumped into the reactor in parallel to perform precipitation reaction. The mass ratio of the cobalt salt solution to the auxiliary feed ② is: Co / M F② =6, the mass ratio of cobalt salt solution to auxiliary feed ③ is: M Co / M F③ =34, the flow rate of solution B is adjusted according to the hydroxide concentration, and the flow rate of C1 is adjusted according to the ammonia concentration, so as to always keep the concentrations of the added sodium hydroxide solution and ammonia solution consistent with those of the bottom liquid in the reactor.
[0063] (8) The slurry obtained in step (7) is filtered and washed to remove excess sulfate ions and lithium ion impurities. When Na≤1000ppm and S≤1000ppm in the sample, the sample is dried to obtain a product C.
[0064] (9) The β-Co(OH)2 product C obtained in step (8) was characterized by SEM. Figure 3 The particle size is 0.1-1.0μm. The larger submicron particles are composed of smaller submicron particles due to dissolution and recrystallization, and appear as thick and long plates with larger lateral dimensions; while the scattered smaller submicron particles appear as thick bricks with smaller lateral dimensions. The distribution uniformity and dispersion are average.
[0065] Embodiment 4: A method for preparing life-type cobalt hydroxide, comprising the following steps:
[0066] (1) According to the concentration of a certain metal cobalt nitrate solution, calculate the corresponding mass of cobalt nitrate, and use pure water to prepare a salt solution with a concentration of 2.2 mol / L, which is recorded as solution A;
[0067] (2) preparing a sodium hydroxide solution with a concentration of 14 mol / L as a precipitant, recorded as solution B;
[0068] (3) Add 50% pure water to the reactor and pass 0.4 m 3 / h nitrogen as protective gas, and then start the stirring and heating program: the stirring speed is 700rpm, the temperature is 50℃, and then a certain amount of liquid alkali and ammonia water are added to adjust the hydroxide concentration in the base liquid to 1.5mol / L, the ammonia concentration to 7.5g / L, the PVP solution concentration to 20g / L, and the DTAB concentration to 5g / L;
[0069] (4) Under the conditions in step (3), solutions A and B are simultaneously pumped into the reactor in parallel to perform a precipitation reaction. The flow rate of solution A is 2 L / h, and the flow rate of solution B is adjusted according to the hydroxide concentration, so that the concentration of the added sodium hydroxide solution is always kept consistent with the concentration of the sodium hydroxide solution in the bottom liquid of the reactor.
[0070] (5) The slurry obtained in step (4) is filtered and washed to remove excess lithium ion impurities. When the Na content in the sample is ≤1000 ppm, the sample is dried to obtain a product D.
[0071] (6) The β-Co(OH)2 product D obtained in step (5) was characterized by SEM. Figure 4The particle size is 0.3-1.0μm. The larger submicron particles are thin but have larger lateral dimensions. The scattered smaller submicron particles are thin and short because of their short growth time. Overall, the distribution uniformity and dispersion are average.
[0072] Example 5 Preparation method of first rate type cobalt (II) hydroxide
[0073] The difference between this embodiment and embodiment 1 is that the stirring speed is 800 rpm, the temperature is 30° C., and then a certain amount of liquid alkali and ammonia water are added to adjust the hydroxide concentration in the base liquid to 1.0 mol / L.
[0074] The remaining preparation conditions are the same as those in Example 1.
[0075] The morphology of the β-Co(OH)2 product E prepared in this example is as follows Figure 5 As shown, the particle size distribution is 0.1-0.5 μm, and individual submicron particles are in the shape of bricks that are slightly thick but smaller in lateral dimensions, with uniform distribution and good dispersion.
[0076] Example 6 Preparation method of comprehensive cobalt hydroxide (II)
[0077] The difference between this embodiment and embodiment 2 is that the stirring speed is 800 rpm, the temperature is 35° C., the concentration of the PVP solution is 13 g / L, and the concentration of the DTAB solution is 5 g / L; the other preparation conditions are the same as those in embodiment 2.
[0078] The morphology of the β-Co(OH)2 product F prepared in this example is as follows Figure 6 As shown, the particle size distribution is 0.1-0.5 μm, and individual submicron particles also appear to be thin and blade-like with small lateral dimensions, with uniform distribution and good dispersion.
[0079] Comparative Example 1: Preparation of amorphous, spherical low-crystalline cobalt hydroxide
[0080] (1) According to a certain concentration of a metal cobalt sulfate salt solution, the corresponding mass of cobalt sulfate is calculated, and cobalt sulfate is prepared with pure water to prepare a metal cobalt sulfate salt solution with a concentration of 2 mol / L, which is recorded as solution A;
[0081] (2) preparing a sodium hydroxide solution with a concentration of 10 mol / L as a precipitant, recorded as solution B;
[0082] (3) According to a certain concentration, calculate the corresponding mass and use pure water to prepare an ammonia solution with a concentration of 10 mol / L, which is recorded as solution C;
[0083] (4) Add 50% pure water to the reactor and pass 0.4 m 3 / h nitrogen as protective gas, and then start the stirring and heating program: the stirring speed is 700rpm, the temperature is 50℃, and then a certain amount of liquid alkali and ammonia water are added to adjust the hydroxide concentration in the base liquid to 0.7mol / L and the ammonia concentration to 1g / L;
[0084] (5) Under the conditions in step (4), solutions A, B, and C are simultaneously pumped into the reactor in parallel to perform a precipitation reaction. The flow rate of solution B is adjusted according to the hydroxide concentration, and the concentration of the added sodium hydroxide solution is always kept consistent with the concentration of the sodium hydroxide solution in the bottom liquid of the reactor.
[0085] (6) The slurry obtained in step (5) is filtered and washed to remove excess sulfate ions and lithium ion impurities. When Na≤1000ppm and S≤1000ppm in the sample, the sample is dried to obtain a product E.
[0086] (7) The β-Co(OH)2 product G obtained in step (6) was characterized by SEM. Figure 7 The particle size is about 1-3μm. Without the appropriate additives, it is difficult to disperse into single submicron particles, but tends to agglomerate into spheres or quasi-spheres. At the same time, due to its poor crystallinity, the submicron grain boundaries are relatively difficult to distinguish.
[0087] Comparative Example 2: Nickel-cobalt-manganese positive electrode material, calculated by molar ratio, Ni:Co:Mn=90:5:5.
[0088] Electrochemical performance test of cobalt hydroxide
[0089] 1. The β-Co(OH)2 prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were physically mixed with nickel-cobalt-manganese positive electrode materials (Ni:Co:Mn=90:5:5 in molar ratio), and annealed at 770°C to prepare different lithium battery positive electrode materials.
[0090] 2. The five prepared positive electrode materials were mixed into slurry according to the mass ratio of positive electrode material: conductive carbon: polyvinylidene fluoride (PVDF) = 90:5:5, and made into positive electrode sheets (the compaction density of the sheet is 3.0 mg / cm 2 ), lithium metal sheet was selected as the negative electrode material, 1MLiPF6 / EC:DMC=1:1 (V%) was used as the electrolyte (EC is ethylene carbonate; DMC is dimethyl carbonate), and a CR2025 button battery was assembled.
[0091] 3. After three cycles of activation at 0.05C rate, the discharge capacity retention rate was obtained by cycling 100 times at 1C rate. Capacity retention rate after 100 cycles (%) = discharge capacity at the 100th cycle / discharge capacity at the 1st cycle × 100%, and the cycle retention rate of the material was obtained, as shown in the table below.
[0092] 4. The rate performance test was carried out according to the charge and discharge program of 0.05C*3+0.1C*3+0.2C*3+0.5C*3+1.0C*3+2.0C*3+5.0C*3. The results are shown in Tables 1 and 2 below.
[0093] Table 1 Comparison of cycle performance of various positive electrode materials
[0094]
[0095] Table 2 Comparison of rate performance of various positive electrode materials
[0096]
[0097] It can be seen from the results in Tables 1 and 2 above that β-Co(OH)2 precursors with different shapes and sizes can be prepared under different experimental conditions, and the positive electrode materials obtained by using them as surface coatings have different electrochemical properties. The smaller the lateral size of the particles and the thinner the primary particles, the higher the cycle performance and the better the rate performance (sample B and sample F); the thicker the particles, the more reliable conductive sub-layers attached to the surface of the particles provide for the positive electrode material, and the better the rate performance (sample A, sample C and sample E); the thinner the primary particles, the wider the area attached to the surface of the secondary particles of the positive electrode material, the more effective the protection performance, and the significantly enhanced cycle life (sample D).
[0098] It can be seen from the above experimental results that the use of β-Co(OH)2 precursors with different micromorphologies and sizes to coat nickel-rich cathode materials can enhance their electrochemical properties from different angles. Specifically, the smaller the lateral size of the submicron sheet / particle of the β-Co(OH)2 precursor and the thinner the primary particle, the more effective the cycling performance and rate performance of the nickel-rich cathode material will be after coating it. The thicker the submicron sheet / particle, the more reliable conductive sublayer attached to the surface of the particle provides for the nickel-rich cathode material, and the higher the improvement in rate performance. The thinner the primary particle, the wider the area of its attachment to the surface of the secondary particle of the nickel-rich cathode material, the more effective the protection performance will be, and the cycle life will be significantly enhanced.
[0099] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a β-Co(OH)2 precursor, characterized in that: The method comprises: in the presence of a complexing agent, a soluble cobalt salt and an alkaline compound are subjected to a coprecipitation reaction in a solvent to obtain a β-Co(OH)2 precursor with different microscopic morphologies and sizes, wherein the complexing agent comprises ammonia water, a long-chain polymer surfactant and a quaternary ammonium salt surfactant.
2. The preparation method according to claim 1, characterized in that: The long-chain polymer surfactant is polyvinyl pyrrolidone, and the quaternary ammonium salt surfactant is dodecyl trimethyl ammonium bromide.
3. The preparation method according to claim 2, characterized in that: The following steps are involved: Under the protection of inert gas, a cobalt salt solution and an alkaline compound solution are simultaneously introduced into a base liquid, wherein the base liquid optionally further contains at least one of a polyvinyl pyrrolidone solution and a dodecyl trimethyl ammonium bromide solution, the concentration of the polyvinyl pyrrolidone solution is 0 g / L-20 g / L, and the concentration of the dodecyl trimethyl ammonium bromide solution is 0 g / L-7 g / L. After a coprecipitation reaction, a β-Co(OH)2 precursor with a particle size of 0.3 μm-1.0 μm is obtained, and the larger single submicron particles are in the form of thin flakes with larger lateral dimensions, while the scattered smaller single submicron particles are in the form of thin and short flakes.
4. The preparation method according to claim 2, characterized in that: The following steps are involved: Under the protection of inert gas, a cobalt salt solution and an alkaline compound solution are introduced into the base liquid in parallel, wherein: in addition to the cobalt salt solution and the alkaline compound solution introduced into the base liquid in parallel, an ammonia solution, a polyvinyl pyrrolidone solution and a dodecyl trimethyl ammonium bromide solution can also be optionally introduced, the concentration of the ammonia solution is 0g / L-5g / L, the concentration of the polyvinyl pyrrolidone is 0g / L-20g / L, and the concentration of the dodecyl trimethyl ammonium bromide is 0g / L-7g / L. After coprecipitation reaction, a β-Co(OH)2 precursor with a particle size of 0.1μm-1.0μm is obtained, and a larger single submicron particle is composed of a single smaller submicron particle spliced together by dissolution and recrystallization, and presents a thick long plate with a larger lateral size; while the scattered single smaller submicron particles present a thick brick shape with a smaller lateral size.
5. The preparation method according to claim 2, characterized in that: The following steps are involved: Under the protection of inert gas, a cobalt salt solution and an alkaline compound solution are passed into a base liquid in parallel, wherein: the base liquid optionally further contains at least one of a polyvinyl pyrrolidone solution and a dodecyl trimethyl ammonium bromide solution, and in addition to the cobalt salt solution and the alkaline compound solution passed into the base liquid in parallel, an ammonia solution, a polyvinyl pyrrolidone solution and a dodecyl trimethyl ammonium bromide solution can also be optionally passed into the base liquid. After a coprecipitation reaction, after the reaction is completed, the concentration of the polyvinyl pyrrolidone solution in the reaction system is 0.01 g / L-30 g / L, the concentration of the dodecyl trimethyl ammonium bromide solution is 0.01 g / L-10 g / L, and the concentration of the ammonia solution is 0.01 g / L-5 g / L, so as to obtain a β-Co(OH)2 precursor with a particle size of 0.1 μm-0.5 μm, and a single submicron particle presents a thick brick shape with a small lateral size or a single submicron particle presents a thin blade shape with a small lateral size.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The preparation of the basic base liquid comprises: adding pure water to a reaction kettle, introducing an inert gas to replace the air, and after the air in the reaction kettle is completely replaced, stirring and heating are turned on, and after the temperature reaches the requirement, ammonia solution and alkali solution are added to the pure water to adjust the pH value of the solution in the reaction kettle, wherein: the stirring speed of the base liquid is 100rpm-1000rpm, and the temperature is 20°C-80°C; the amount of pure water used is 20%-60% of the total volume of the reaction kettle, the alkali solution is a sodium hydroxide solution, the hydroxide concentration in the base liquid is 0.001mol / L-2.0mol / L, and the ammonia solution concentration is 1g / L-10g / L.
7. The preparation method according to any one of claims 3 to 5, characterized in that: The soluble cobalt salt includes at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate. The concentration of the soluble cobalt salt solution is 1 mol / L-3 mol / L. The alkaline compound is sodium hydroxide. The concentration of the alkaline compound solution is 5 mol / L-14 mol / L. The mass ratio of the cobalt element in the soluble cobalt salt solution to the polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution is 5-30. The mass ratio of the cobalt element in the soluble cobalt salt solution to the dodecyltrimethylammonium bromide in the dodecyltrimethylammonium bromide solution is 30-120.
8. The preparation method according to any one of claims 3 to 5, characterized in that: Also includes: After the coprecipitation reaction is completed, the slurry is aged, filtered, centrifuged and washed until the Na content in the material is ≤1000ppm and the anion content is ≤1000ppm, and then dried to a moisture content of ≤0.8% to obtain a β-Co(OH)2 precursor.
9. A β-Co(OH)2 precursor prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The β-Co(OH)2 precursor has a monomer lamellar structure and an average particle size of 0.1 μm-5.0 μm.
10. A lithium battery positive electrode material, characterized in that: The surface of the lithium battery positive electrode material is coated with the β-Co(OH)2 precursor prepared by the preparation method described in any one of claims 1 to 8 or the β-Co(OH)2 precursor described in claim 9.